Tracing the geographic origin of velvet antlers in China via stable isotope analyses. Issue 27 (13th June 2022) - Zhao, Haiping; Zhang, Guokun; Wang, Dongxu; Liu, Zhen; Chen, Rui; Zhang, Wei; Li, Chunyi
Abstract : Multielement (H, C, N, O) stable isotope ratio analysis was used to discriminate the geographical origin of velvet antlers (VAs) of deer from ten provinces in China. Abstract : Multielement (H, C, N, O) stable isotope ratio analysis was used to discriminate the geographical origin of velvet antlers (VAs) of deer from ten provinces in China. Ratios of 2 H/ 1 H, 13 C/ 12 C, 15 N/ 14 N, and 18 O/ 16 O in the VA samples were measured using isotope ratio mass spectrometry. The results showed that there were highly significant differences in the mean isotopic values and in four isotopic ratios between VA samples from the ten provinces. The most significant difference among the four isotope ratios was in δ 2 H ratio of VA samples; regions with a more humid climate and higher average ambient temperatures had higher δ 2 H ratios than those with dry climates and lower temperatures. These results demonstrate that the multiple stable isotopic ratio approach is a powerful tool to help trace the geographical origin of VAs, and could be adopted by government officials to help protect consumer interests from improper labeling in VA markets.